Uncertainty in maternal exposures to ambient PM2.5 and benzene during pregnancy: Sensitivity to exposure estimation decisions. (May 2016) - Tanner, Jean Paul; Salemi, Jason L.; Stuart, Amy L.; Yu, Haofei; Jordan, Melissa M.; DuClos, Chris; Cavicchia, Philip; Correia, Jane A.; Watkins, Sharon M.; Kirby, Russell S.
Highlights: We estimate maternal exposure to two air pollutants using ambient measurement data. We compare estimates using alternative exposure assessment choices. Estimates were sensitive to assessment decisions, but differences were unbiased. Estimates were most sensitive to the time scale used to represent exposure. Exposure class changed by one quartile or more for up to about a third of mothers. Abstract: We investigate uncertainty in estimates of pregnant women's exposure to ambient PM2.5 and benzene derived from central-site monitoring data. Through a study of live births in Florida during 2000–2009, we discuss the selection of spatial and temporal scales of analysis, limiting distances, and aggregation method. We estimate exposure concentrations and classify exposure for a range of alternatives, and compare impacts. Estimated exposure concentrations were most sensitive to the temporal scale of analysis for PM2.5, with similar sensitivity to spatial scale for benzene. Using 1–12 versus 3–8 weeks of gestational age as the exposure window resulted in reclassification of exposure by at least one quartile for up to 37% of mothers for PM2.5 and 27% for benzene. The largest mean absolute differences in concentration resulting from any decision were 0.78 µg/m 3 and 0.44 ppbC, respectively. No bias toward systematically higher or lower estimates was found between choices for any decision.